The Influence of Carbohydrate Structure on the Clearance of Recombinant Tissue-Type Plasminogen Activator - Hotchkiss, A; Refino, C J; Leonard, C K; O'Connor, J V; Crowley, C; McCabe, J; Tate, K; Nakamura, G; Powers, D; Levinson, A; Mohler, M; Spellman, M W (Thrombosis and Haemostasis, 1988)
Modification of the carbohydrate structures of recombinant tissue-type plasminogen activator (rt-PA) can increase or decrease its rate of clearance in rabbits. When rt-PA was treated with sodium periodate to oxidize carbohydrate residues, the rate of clearance was decreased from 9.6 ± 1.9 ml min−1 kg−1 to 3.5 ± 0.6 ml min−1 kg−1 (mean ± SD, n = 5). A similar change in the clearance of rt-PA was introduced by the use of endo-β-N-acetyl- glucosaminidase H (Endo-H), which selectively removes high mannose asparagine-linked oligosaccharides; the clearance of Endo-H-treated rt-PA was 5.0 ± 0.5 ml min−1 kg−1. A mutant of rt-PA was produced with an amino acid substitution at position 117 (Asn replaced with Gin) to remove a potential glycosylation site that normally contains a high mannose structure. The clearance of this material was also decreased, similar to the periodate and Endo-H-treated rt-PA. Conversely, when rt-PA was produced in the CHO 15B cell line, which can produce only high mannose oligosaccharide structures on glycoproteins, the clearance was increased by a factor of 1.8. These results demonstrate that the removal of rt-PA from the blood depends significantly upon the nature of its oligosaccharide structures.
Keywords: Tissue-type plasminogen activator; Plasminogen activator; Pharmacokinetics; CHO 15 B cells; High mannose oligosaccharides